The investigation of side-weir siphons flow along a curved channel - Ozturk, M.; Yucel, A.; Tuna, M. C. (Academic Publication Council, 2015)
Side weirs are being used commonly in irrigation, field drainage, sewage systems, side channel spillway dams and settling basins to supply needed discharge or put away excess discharge without giving harm to the environment. In this study, self-priming siphon was used instead of side weir. Settled in the different angels (30 degrees, 60 degrees and 90 degrees) of a curved channel and flat side (0 degrees), water level and velocity were measured by opening and closing of the regulating level gate in different discharges and levels. At the result of these measurements, water surface profiles and depth averaged velocities were found and shown in figures. Froude numbers, siphon spillway discharge and discharge coefficients were calculated. In addition, siphon spillway and priming, depriming and helicoidal flow were investigated.
Keywords: Depth averaged velocities; Priming and depriming; Side weir; Siphon spillway; Water surface profiles